Influence of the Jet Air Flow with Inclined Plate under Corona Discharge - Saneewong Na Ayuttaya, Suwimon (Science & Technology Asia, 2020)
In this research paper, the influence of the jet air flow with an inclined plate is investigated under corona discharge. The number of electrodes is varied in the range 1 - 6. The high electrical voltage and angle of inclined plate are tested in a range of 0 – 30 kV and 0 – 90o, respectively. The jet air flow is fixed at 1 m/s. The first part of the experimental results showed that the pressure, the gravity force and the impact velocity under corona discharge are increased with increasing electrical voltage, the number of electrodes and angle of the inclined plate. This is because the strength of corona discharge is increased by increasing the electrical voltage and number of the electrodes. The pressure ratio and gravity force ratio are decreased with an increasing angle of the inclined plate because the effect of trap of airflow is dominantly influenced by increasing the angle of inclined plate. In addition, the maximum pressure, the gravity force and the impact velocity under corona discharge are 2.11, 5.24 and 1.88 times, respectively, in comparison with no corona discharge. The second part of the comparison between experimental and numerical results showed that the pressure and the impact velocity under corona discharge are increased with an increasing electrical voltage and the angle of the inclined plate. The impact velocity under corona discharge is dominantly increased by the electrical voltage increasing. Finally, a similar trend of the graph has appeared for experimental and numerical results so simulation results had good agreement with experiment results.